Between Dixie and Zion: Southern Baptists and Palestine before Israel - Robins, Walker (Religion and American culture, 2020)
Before the Palestine question -- Travelers -- Arabs -- Missionaries -- Jew -- Auxiliaries -- Premillennialists -- Fundamentalist -- Commentators -- Cyrus.